PENGARUH METODE PERMAINAN MENGGUNAKAN PARASUT DALAM PEMBELAJARAN PENJAS TERHADAP PENINGKATAN KEPERCAYAAN DIRI SISWA TUNARUNGU - Solihin, Akhamad Olih (Jurnal Olahraga, 2015)
The purpose of this study was to determine differences in self-confidence scores between deaf students who studied with the game method using Parachutes and conventional methods of deaf students in SLB Negeri Citeureup, Cimahi City. The research method used to uncover these problems through the experimental method with Pretest-Posttest Control Group Design. The sample of this study was deaf students of middle and high school who were taken by Saturated Sampling in SLB Negeri Citeureup, Cimahi City. The study was conducted 3 meetings each week for 8 weeks. The instrument used was a confidence questionnaire that had been tested for validity and reliability. The data obtained were processed using the T-Paired test. The results of the study revealed that there were significant differences in the pretest and posttest scores of self-confidence between deaf students who studied with the game method using Parachutes and conventional methods. Further research was to examine the use of equipment other than parachutes to develop the ability to be deaf.